Determining the relationship between food texture and dental condition: First bite and chewing aspects. (September 2022) - Aktar, Tugba; Karci, Bilge; Citir Yucel, Hande; Ergin, Firuze
Abstract: Among the sensory properties of foods, texture perception is a complex modality due to catastrophic changes during eating. Relating dental conditions and capacity of texture sensation are still paucities in the literature. Different dental areas emphasize the difference in texture sensation. Anterior teeth are responsible for biting, ripping or tearing; while posterior teeth are chewing and grinding. Hence, the absence of any is expected to cause disruptions in mastication functions. The hypothesis of the present study was dental loss or missing is a burden for hardness perception for first-bite and twice chewed for anterior and posterior teeth, respectively. Patient groups were divided according to anterior-posterior tooth deficiencies and hardness sensation was assessed at first bite and twice chewed modal food (white cheese) with various hardness levels obtained with different fat content. The modal food was tested for its physicochemical, textural and sensory properties with dental assessment. Findings suggest that first-bite hardness judgements were not affected by the loss of the anterior. Oppositely, twice chewed hardness has a significant effect on the loss of a posterior tooth. These findings can indicate to future researchers to be tested according to their dental status especially if chewing is necessary for their sensory tests. Highlights: Dental status and teeth loss is expected to alter/limit the texture perception. Anterior teeth loss is likely to compensate sensation loss with neighbouring anterior. First-bite hardness judgements were not affected by the loss of the anterior teeth. Perceived hardness is correlated with loss of a posterior teeth. Dental status affects the hardness sensation, specifically for the chewing hardness sensation.